J.F. Shafroth papers - Shafroth, J. F. (John Franklin), 1887-1967.
Official correspondence, memoranda, directives, and reports sent to William Frederick Halsey and Chester W. Nimitz, relating primarily to Shafroth's experiences as a commander in the South Pacific during World War II and head of a task group which conducted the first heavy bombardment of Japan. Includes material relating to Shafroth's course work at the Army War College (U.S.). Correspondents include William Frederick Halsey, John B. Heffernan, and Chester W. Nimitz.
Chiefly mimeograph or carbon copies.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Halsey, William Frederick, -- 1882-1959.; Halsey, William Frederick, -- 1882-1959 -- Correspondence; Heffernan, John B. -- Correspondence; Nimitz, Chester W. -- 1885-1966.; Nimitz, Chester W. -- 1885-1966 -- Correspondence; United States. -- Navy; Army War College (U.S.); World War, 1939-1945 -- Campaigns -- Japan; World War, 1939-1945 -- Campaigns -- Pacific Ocean; Naval officers